Nghiên cứu sự phân huỷ của vật liệu tổ hợp polylactic axit/chitosan có và không có polycaprolacton - Thu Trang, Nguyễn Thị; Chinh, Nguyễn Thúy; Hoàng, Thái (Vietnam Journal of Chemistry, 2016)
Polylactic acid (PLA) and chitosan (CS) are two natural resource polymers which have been applied widely into different fields. Polylactic acid (PLA) and chitosan (CS) has been attracted by many researcher due to their good adhesion, biodegradability and biocompatibility. This study expresses hydrolysis of PLA/CS composite with and without polycaprolactones (PCL) as a compatibilizer in acid environment and phosphate buffer solution. The PLA/CS composites were characterized by Fourier Infrared Spectra (FTIR), Scanning Electron Microscopy (SEM) and Differential Scanning Calorimetry (DSC). The hydrolysis of PLA/CS/PCL composites in acid solution (0.1 N) and phosphate buffer solution (pH = 7.4) for different times was also investigated. The content PCL of 6- 8 %wt. is suitable for preparing PLA/CS nanocomposites. Keywords. Polylactic acid, chitosan, polycaprolacton, hydrolysis, weight loss.